FACTORS AFFECTING THE SELLING PRICE OF BEEF IN TRADITIONAL MARKETS IN MERAUKE REGENCY - Ferdinand Christianto Situmorang; Kristianus Hiktaop; Gardis Andari (SEAN Institute, 2022)
This research is a field survey research on traditional traders at Wamanggu Market and Evening Market in Merauke Regency. And treated as a population, while the sample is selected randomly or by chance. This research is to analyze how the influence of beef production, the number of imported cattle, demand for beef and the price of beef in the previous month on the price of beef in the Merauke Regency Traditional Market. Research data was collected in the form of questionnaires and questionnaires. The research was carried out from June 2021 to December 2021. The results showed that the factors that affect the price of beef in Merauke Regency are the number of imported cattle, the demand for beef and the price of beef in the previous month. has a real positive effect on the price of beef in Merauke Regency. Beef production has a negative and not significant effect on beef prices in Merauke Regency